Emerging concern of supportive supervision in hospital waste management: A formative delphi study - Markus Kaban; Suhartono Suhartono; Purwanto Adhi Pireno; Alberta Widya Kristanti; Perigrinus Hermin Sebong (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Improper management of all types of hospital waste has become a significant problem relevant to public health issues. However, even though there are regulations regarding waste management, the implementation still varies between hospitals. The most neglected factor is the waste management supervision frameworks.  Purpose: To identify the emerging concern of supportive supervision in hospital waste management. Method: This formative delphi study employed qualitative methods and focus group discussions (FGDs). Each FGD lasted 60 minutes. The study incorporated the concept of stakeholder engagement in hospital waste governance, focusing on factors driving stakeholder participation, knowledge-sharing structures, information exchange, decision-making processes, and the institutionalization of various centers of power and decision-making to diversify waste management oversight. Results: Participants were most likely to decide to improve waste management. Of the 18 questions, three received a higher number of "yes" responses (53.8%). The first question concerned managers in the environmental, occupational safety, and health department providing recognition/appreciation for staff performance or achievements in waste management at the hospital. The second question concerned information provided by managers to staff regarding open and periodic performance appraisals. The third question concerned the use of audit results to improve the existing waste management system. Conclusion: Supervision is an activity aimed at improving service quality. It requires a conditional and open environment to accept problem-solving. To enhance the quality of service, supervision must be systematic and require continuous follow-up.